Registro y medición de las transacciones y la razonabilidad de los estados financieros de las constructoras de ingenierías eléctricas - Quinteros Sandoval, Katherine Gisselle (2023)
Currently, the country is going through a difficult economic situation that directly affects the Companies, generating the hiring of unskilled labor, multifunctional personnel, uncollectible portfolios and inconvenience with the automation of commercial transactions. It is important to indicate that the financial information is formed from the commercial transactions carried out on a day-to-day basis that, in the event of any error or inefficiency in the processes, can directly affect the financial statements. Due to the inconvenience that has been generated by the recovery of the portfolio, the Company is opting for the post-dated check as a collection method, the same as if they do not have a correct application, custody and registration, errors can be generated, affecting the accounts accounting involved, as well as the flow of the Company..............